2011
DOI: 10.1097/inf.0b013e3181f10fff
|View full text |Cite
|
Sign up to set email alerts
|

Three Children With Plastic Bronchitis Associated With 2009 H1n1 Influenza Virus Infection

Abstract: We report the cases of 3 children with plastic bronchitis associated with 2009 H1N1 influenza virus infection. These 3 children shared common clinical and radiologic features: rapid and progressive respiratory distress with whole lung atelectasis on chest radiograph. In children with severe respiratory symptoms accompanied by H1N1 influenza, plastic bronchitis should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…The result of the current study indicating the higher frequency of mucoid impaction in patients with n-IFV pneumonia could be supported by the reports which have shown cases of plastic bronchitis in patients with n-IFV pneumonia [21][22][23]. Plastic bronchitis is typically a rare condition characterized by the presence of large, thick, mucofibrinous plugs filling the bronchial tree, resulting in extensive atelectasis, and is seen relatively frequently in patients with n-IFV pneumonia in Japan [22].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The result of the current study indicating the higher frequency of mucoid impaction in patients with n-IFV pneumonia could be supported by the reports which have shown cases of plastic bronchitis in patients with n-IFV pneumonia [21][22][23]. Plastic bronchitis is typically a rare condition characterized by the presence of large, thick, mucofibrinous plugs filling the bronchial tree, resulting in extensive atelectasis, and is seen relatively frequently in patients with n-IFV pneumonia in Japan [22].…”
Section: Discussionsupporting
confidence: 75%
“…We believe that CT is necessary when the condition of patients rapidly progresses due to DAD or airspace consolidation with volume loss caused by mucoid impaction or plastic bronchitis because the early intervention is necessary in these situations. Actually, airspace consolidation with volume loss caused by mucoid impaction tends to improve with the early intervention [21][22][23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al, 12 Deng et al, 23 and Terano et al 24 reported that plastic bronchitis occurred in patients with S-OIV. Our institution had a CT examination of one patient with plastic bronchitis that was proven by bronchoscopy.…”
Section: Discussionmentioning
confidence: 98%
“…Influenza A has recently been identified for its association with PB, especially during the recent 2009 outbreak of the H1N1 influenza A pandemic in Asia and Mexico [4][5][6][7][8][9][10][11]. Children with influenza A infection can frequently develop acute pulmonary complications and sequelae such as pneumonia and acute respiratory failure when acutely infected.…”
Section: Introductionmentioning
confidence: 99%